Socio-demographic and geographic disparities of population-level food insecurity during the COVID-19 pandemic in Thailand - Phulkerd, Sirinya; Thongcharoenchupong, Natjera; Chamratrithirong, Aphichat; Gray, Rossarin Soottipong; Pattaravanich, Umaporn; Ungchusak, Chantana; Saonuam, Pairoj (Frontiers in Public Health, 2023)
Introduction This study investigated the prevalence of food insecurity, and the association between socio-demographic and geographic factors and food insecurity in Thailand during the COVID-19 pandemic. Methods The study extracted data on 5,066 persons age 15 years or older from a nationally-representative sample survey of Thai households, conducted during June-December 2021. The respondents were asked about food insecurity, socio-demographic characteristics, debt, and role of the primary household food provider. Binary logistic regression analysis was used to investigate the association between the variables and food insecurity. Results Of the total sample, 28.6% had food insecurity. The highest probability of having food insecurity (p < 0.001) was observed in persons age 15–29 years, with no formal education, and in the lowest quartile of income. The highest probability of having food insecurity was found among respondents residing in the northeast, which is the poorest and with the least development status among geographic regions in Thailand. Respondents who reported having onerous personal debt and being the main household food provider were 1.4 and 2.3 times as likely to have food insecurity as those with no debt and not being the main food provider, respectively (p < 0.001). Conclusion This suggests that government attention is required in developing policies and strategies to improve food security through addressing the socio-economic determinants, and buffer the negative impact of a national crisis on diets. Investment to improve household income and raise the educational profile of the population is needed. Addressing the regional disparities in food security requires area-specific measures which target the most vulnerable population groups.